Zero - Mikesh, Robert C. (Motorbooks International warbird history, 1994)
The most in-depth combat and development history of the Japanese Zero ever assembled! This superb history is told through first-person interviews with Zero pilots and the U.S. airmen who fought against them. Includes cutaway drawings, serial number lists, detailed appendices, and a registry of surviving planes. Contains exquisite cutaway drawings by Rukyu Watanabe. Foreword by Saburo Sakai.